2008
DOI: 10.3402/ijch.v67i2-3.18271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of special diabetes program for Indians funding on system changes in diabetes care and outcomes among American Indian/Alaska Native people 1994–2004

Abstract: Objectives. The Alaska Native Medical Center diabetes program analysed Diabetes Care and Outcomes Audit data from 1994-2004 to evaluate the impact of the Special Diabetes Program for Indians (SDPI) funding on process and intermediate outcomes. Study Design. We conducted a retrospective analysis of data from standardized medical records reviews conducted between 1994 and 2004 from regional sites in Alaska. Methods. We analysed 7,735 randomly selected records for trends over three time periods (pre-SDPI, transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 14 publications
4
27
1
Order By: Relevance
“…The monitoring found in the present study was of lesser quality than reported recently in the follow-up study after implementation of the Special Diabetes Program for Indians (12). Screening rates after implementation within 12 months were 85% (lipid profile), 67% (foot exam) and 56% (eye exam).…”
Section: Management Of Diabetes Care In Greenlandcontrasting
confidence: 51%
“…The monitoring found in the present study was of lesser quality than reported recently in the follow-up study after implementation of the Special Diabetes Program for Indians (12). Screening rates after implementation within 12 months were 85% (lipid profile), 67% (foot exam) and 56% (eye exam).…”
Section: Management Of Diabetes Care In Greenlandcontrasting
confidence: 51%
“…It is possible that improving metabolic control is contributing to our lower rate over time compared to other populations. Data from the Diabetes Standards of Care and Outcomes audit showed that mean HDL has increased; mean systolic and diastolic blood pressures, hemoglobin A1c, total cholesterol, low-density lipoproteins and triglycerides have steadily declined from 1994 to 2004 among Alaska Native people with diabetes (6). The lower amputation rates seen in our population may be due to an increase in the number of people with a shorter duration of diabetes.…”
Section: Amputationsmentioning
confidence: 48%
“…This decrease was true even when duration of diabetes was taken into account (35). It is possible that our renal replacement and death rate has decreased due to improved control of blood sugar and blood pressure as well as increased use of renal-protective medications, as has been observed among Pima Indians, other south-west U.S. Indians and the Indian Health Service as a whole (6,(35)(36)(37). Renal failure rates may appear lower if patients die of CVD prior to starting dialysis or if they die of diabetic renal failure (36).…”
Section: Renal Replacementmentioning
confidence: 83%
See 2 more Smart Citations